2008
DOI: 10.1002/eji.200737899
|View full text |Cite
|
Sign up to set email alerts
|

Protein/DNA vaccine‐induced antigen‐specific Treg confer protection against asthma

Abstract: Asthma is a chronic inflammatory disorder caused by T-cell-mediated inflammation within airways. No antigen-specific treatment has been available. Using an OVA-induced murine asthma model, we find that co-immunization of an OVA epitope peptide with a DNA vaccine encoding the same epitope is able to prevent this experimental asthma as evidenced in the marked reduction of infiltrations of eosinophils and lymphocytes into the site of the allergen challenge. We demonstrate that the prevention of experimental asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Inflammatory bronchitis was induced in BALB/c mice as described previously (12,15). Autoimmune ovarian disease (AOD) was induced in C57BL/6 mice as described previously (11).…”
Section: Induction Of Inflammatory Bronchitis and Autoimmune Ovarian mentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory bronchitis was induced in BALB/c mice as described previously (12,15). Autoimmune ovarian disease (AOD) was induced in C57BL/6 mice as described previously (11).…”
Section: Induction Of Inflammatory Bronchitis and Autoimmune Ovarian mentioning
confidence: 99%
“…These DCregs could convert naive T cells into Agspecific regulatory T cells (iTregs) of a CD4 + CD25 2 Foxp3 + IL-10 + phenotype in vitro and in vivo (8), which in turn mediated Ag-specific tolerance (8)(9)(10)(11)(12). Given the role of these DCregs in initiating the tolerogenic process, we wish to understand how they are generated during coimmunization.…”
mentioning
confidence: 99%
“…The immunization induced antigen-specific CD4 + CD25 − asTregs and prevented the host from OVA sensitization-induced asthma (33). To evaluate the therapeutic value of this protocol in established asthma, we induced airway inflammation in BALB/c mice by multi-step sensitization/challenging of intranasal injection of OVA (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…On day 14, asthma of recipients was evaluated. Plethysmography was analyzed as reported (33). Briefly, mice were anesthetized and ventilated.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is difficult to determine whether or not the therapies are directly and colleagues has demonstrated that co-administration of a protein with DNA coding for that protein can confer protection to allergic and autoimmune diseases through the induction of regulatory T-cells. [116][117][118] This group additionally demonstrated the converse that regulatory T-cells could be inhibited and the immunogenicity of vaccination increased through use of an inhibitor of regulatory T-cells as an adjuvant. 119 Thereby demonstrating the vast range of combinatorial possibilities with DNA-based vaccination approaches to either increase or suppress immune responses.…”
Section: Current Clinical Trialsmentioning
confidence: 99%